Sediment elemental data (XRF) of sediment core GeoB19905-1 - Jens Weiser; Jürgen Titschack; Markus Kienast; I Nick McCave; Annalena Antonia Lochte; Jeetendra Saini; Ruediger Stein; Dierk Hebbeln (PANGAEA, 2021)
XRF Core Scanner data of sediment core GeoB19905-1 were collected every one to two centimetres downcore over an active area of 15 mm^2 with a downcore slit size of 10 mm using generator settings of 10 and 30 kV directly at the split core surface of the archive half with XRF Core Scanner II (AVAATECH Serial No. 2) at MARUM, Bremen.